Technical and structural efficiency in Mexican manufacturing: A regional approach - Juan Carlos Chávez; Felipe J. Fonseca (Banco de México, 2012)
This paper applies a stochastic frontier approach to analyze the evolution of technical efficiency in manufacturing as a source of regional growth, taking as a unit of analysis the Mexican states in the period 1988-2008. The main findings of our analysis are threefold. First, technical efficiency was increasing over the analyzed period and acted as a mechanism to reduce the labor productivity gap across states. Second, Mexican regions can increase manufacturing production about one third, on average, using the same amount of inputs which implies ample potential for regional growth. Third, there exists a considerable difference in the level of technological development, measured in terms of structural efficiency, of the north and the central regions with respect to the south that partially explains the labor productivity gap among regions.
Keywords: D24; L60; O18; 330; Manufacturing; Mexican regions; Stochastic frontier; Structural efficiency; Technical efficiency; Regionales Wachstum; Technische Effizienz; Verarbeitendes Gewerbe; Mexiko